Does a fibrin-collagen patch support early anastomotic healing in the colon? An experimental study - Ozel, S.K.; Kazez, A.; Akpolat, N. (My University, 2006)
Background: Efficacy of biomaterials over intestinal anastomosis to enhance anastomotic integrity, is still controversial in clinical practice. The aim of this study was to evaluate the effect of absorbable fibrin-collagen patch (FCP) during early colonic anastomotic healing in rats. Methods: Prepuberal Wistar albino rats were randomly divided into 6 groups of 6 rats each. Colon was transected and then anastomosed with sutures (Group A), sutures+FCP (TachoComb; Nycomed, Austria) (Group AT) or only FCP (Group T). Rats were sacrificed either 3 or 7 days after the anastomosis. Anastomoses were evaluated for perianastomotic adhesion formation, bursting pressures and histological features. Results: Perianastomotic adhesion formation was prominent in Groups AT and T. Bursting pressures were in higher group AT than in Group A on postoperative day 3 and lower on day 7 (p<0.05). Histological examinations revealed an increase in inflammatory cells in Group T on day 3 and decreased wound healing in Group AT when compared to Group A on day 7 (p<0.05). Conclusions: In the early period of anastomotic healing, FCP supports anastomotic integrity. However, it also causes an inflammatory reaction which may increase the time necessary for healing process. Thus, the use of this biomaterial should be preferred in only selective clinical cases with a careful follow-up.
Keywords: Biomaterials; Colonic anastomosis; Experimental study; Wound healing